Vertigo temporis. Ruines et autres mascarades d’après Günther Anders - Gangemi, Rosanna (Dialogoi. Rivista di studi comparatistici, 2022)
Günther Anders, who was born in Breslau in 1902 and died in Vienna in 1992, is one of the greatest thinkers on the dangers of modernity. Best known for his theorization of human obsolescence and his philosophy of the bomb, he has nevertheless remained a little-known thinker. If he is one of the few philosophers known first as “the husband of”, in this case Hannah Arendt (from 1929 to 1937), this did not particularly help him to be read and translated. Moreover, in his opus magnum on the obsolescence of man, published in 1956 and which only crossed the Rhine in 2002, he makes a very ominous statement: our technical power has definitely escaped us and there is no remedy. His Diaries of Exile and Return – still little commented on, they belong to the prehistory of his thought and are a chronological and thematic assembly of notes he wrote during his years in migration and beyond, without however yielding to the temptation to talk about himself in an intimate way – and in particular the part entitled Ruins today, will be the subject of this contribution.